EVERYDAY QURâAN DI ERA POST-KONSUMERISME MUSLIM - Saputro, M. Endy (Program Studi Perbandingan Agama, Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri (UIN) Sunan Ampel Surabaya, 2015)
This paper aims to give a preliminary draft to formulate an innovative concept in the Qurâanic studies world in the age of post-consumerism Muslim. Recent studies on tug of war between globalization and religion have been identifying salient social transformation in some parts of Muslim world, such as the rise of new (media) religious authority, religious commodification trends, varieties of Islamic consumption, the emergence of public Islam and so forth. Apart from these recent scholarships, which successfully grasp the globalizationâs influence toward religion (Islam), this paper offers the concept of everyday Qurâan as an alternative basic approach of understanding the cultures of Qurâan in this changing (Muslim) world and at the same time, seeking to briefly explain its emerging issues. Some exemplary issues then have analytically discussed to reflect how the proposed theory applied. Thus, everyday Qurâan can contribute the discourse of cultures based technology in the context of Qurâanic Studies.